Maxwell–Stefan diffusion asymptotics for gas mixtures in non-isothermal setting. (August 2017) - Hutridurga, Harsha; Salvarani, Francesco
Abstract: A mathematical model is proposed where the classical Maxwell–Stefan diffusion model for gas mixtures is coupled to an advection-type equation for the temperature of the physical system. This coupled system is derived from first principles in the sense that the starting point of our analysis is a system of Boltzmann equations for gaseous mixtures. We perform an asymptotic analysis on the Boltzmann model under diffuse scaling to arrive at the proposed coupled system.